2020
DOI: 10.1016/j.joca.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for osteoarthritis pain and chronic low back pain treatments in the United States: a discrete-choice experiment

Abstract: Objective: To quantify preferences for attributes of potential analgesic treatments for moderate-to-severe pain associated with osteoarthritis (OA) and/or chronic low back pain (CLBP) as relevant to injectable nerve growth factor (NGF)einhibitors, nonsteroidal anti-inflammatory drugs (NSAIDs), and opioids. Methods: We used a discrete-choice experiment (DCE) to elicit preferences for attributes of OA and CLBP pharmaceutical treatments, and a best-worst scaling (BWS) exercise to further characterize the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…However, it is very hard for patients to comprehend the concept of the cost-effectiveness of medical technologies. As shown in patient-centered surveys [49][50][51], effectiveness and cost were often treated as independent attributes of medical technologies. Consequently, patients' perceived clinical and economic values of health insurance were considered in our study.…”
Section: Patients' Perceived Value Of Health Insurance Coveragementioning
confidence: 99%
“…However, it is very hard for patients to comprehend the concept of the cost-effectiveness of medical technologies. As shown in patient-centered surveys [49][50][51], effectiveness and cost were often treated as independent attributes of medical technologies. Consequently, patients' perceived clinical and economic values of health insurance were considered in our study.…”
Section: Patients' Perceived Value Of Health Insurance Coveragementioning
confidence: 99%
“…9,10 Other studies found that patients were more concerned about the risk of side effects. [11][12][13] Costs and mode of administration have also been shown to be predictors of preferences in some studies. [14][15][16][17] Therefore, eliciting patients´ preferences for OA treatment may enable therapists to better develop and implement patient-oriented treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings contrast with research on chronic pain, for which patients often rank avoidance of adverse effects as one of the most important factors when devising pain control regimens. 6 , 7 , 17 For example, in a DCE of patients with chronic osteoarthritis, the highest-ranking attribute was symptom control, followed by risk of addiction. 17 Meanwhile, our study of acute pain control found that the potential for adverse effects was less important than pain relief or risk of addiction.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 17 For example, in a DCE of patients with chronic osteoarthritis, the highest-ranking attribute was symptom control, followed by risk of addiction. 17 Meanwhile, our study of acute pain control found that the potential for adverse effects was less important than pain relief or risk of addiction. Furthermore, unlike patients with chronic pain, who may use opioids after finding other treatment modalities ineffective, patients with acute postoperative pain are often prescribed opioids despite the availability of effective, yet less addictive medications.…”
Section: Discussionmentioning
confidence: 99%